2017
DOI: 10.1051/matecconf/201712112012
|View full text |Cite
|
Sign up to set email alerts
|

The function of mirror neurons in the learning process

Abstract: In the last years, Neurosciences have developed very much, being elaborated many important theories scientific research in the field. The main goal of neuroscience is to understand how groups of neurons interact to create the behavior. Neuroscientists studying the action of molecules, genes and cells. It also explores the complex interactions involved in motion perception, thoughts, emotions and learning. Brick fundamental nervous system is the nerve cell, neuron. Neurons exchange information by sending electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…Bu, başkalarının gördüklerini ve hissettiklerini görerek ve hissederek öğrenmenin bir yoludur. 26 Bu çocukluk döneminde eğitim süreci, öğretmen-öğrenci arasındaki ve öğrenci-öğrenci arasındaki ilişki gibi her zaman kişiler arası ilişkileri içerdiğinden, bu süreçte ayna nöronlar önemli bir rol oynamaktadır. Ayna nöronların çalışma şekli ve etki alanları, çocukların öğrenme ortamının ve okuldaki kişiler arası iletişimin geliştirilmesine katkıda bulunmaktadır.…”
Section: Motor öğRenmedeki Rolüunclassified
See 1 more Smart Citation
“…Bu, başkalarının gördüklerini ve hissettiklerini görerek ve hissederek öğrenmenin bir yoludur. 26 Bu çocukluk döneminde eğitim süreci, öğretmen-öğrenci arasındaki ve öğrenci-öğrenci arasındaki ilişki gibi her zaman kişiler arası ilişkileri içerdiğinden, bu süreçte ayna nöronlar önemli bir rol oynamaktadır. Ayna nöronların çalışma şekli ve etki alanları, çocukların öğrenme ortamının ve okuldaki kişiler arası iletişimin geliştirilmesine katkıda bulunmaktadır.…”
Section: Motor öğRenmedeki Rolüunclassified
“…27 Yeni becerileri kavramada taklit etme söz konusu olduğunda ayna nöronlar ön plana çıkmaktadır. 26 En yaygın kullanılan öğrenme biçimlerinden olan taklit, birçok becerinin deneme yanılma yoluyla öğrenmenin zaman alıcı süreci olmadan edinilmesini sağlamaktadır. Taklit, aynı zamanda yüz ve diğer vücut hareketlerini okumak ve diğer insanların amaçlarını, niyetlerini ve arzularını anlamak gibi temel sosyal becerilerin geliştirilmesinde de temel yapı taşıdır.…”
Section: Motor öğRenmedeki Rolüunclassified
“…What seemed pertinent in connection with this question is the recent realization of so-called mirror neurons in the human brain, discovered by Rizzolatti and Sinigaglia [20]. Such neurons are implicated in the ability of an individual to understand another individual's emotion and to empathize by activating neuronal circuits, as when the receiving individual experienced the other person's emotion herself or himself directly [21]. Originally seen in connection with visual or odoriferous stimulation, mirror neurons are now also thought to play a role in adopting emotions that are expressed figuratively, i.e., in idioms, as mirror neurons are located near the Broca area of speech development in the human brain and thereby can facilitate the learning process as well as verbal communication [21].…”
Section: Introductionmentioning
confidence: 99%
“…Such neurons are implicated in the ability of an individual to understand another individual's emotion and to empathize by activating neuronal circuits, as when the receiving individual experienced the other person's emotion herself or himself directly [21]. Originally seen in connection with visual or odoriferous stimulation, mirror neurons are now also thought to play a role in adopting emotions that are expressed figuratively, i.e., in idioms, as mirror neurons are located near the Broca area of speech development in the human brain and thereby can facilitate the learning process as well as verbal communication [21]. The emotional state of the 'receiver individual' according to Bastiaansen et al [13] comes to resemble that of the 'sending individual', especially if a facial expression of disgust [22] accompanies the utterance of a particular idiom.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, studies showed that humans have a mirror neuron system similar to monkeys which are triggered during both action and observation (1,6). Mirror neurons are an integral part of child development because many behaviors and habits are processed, developed, and coded through mirror neuron activation (6). For example, when someone smiles at a baby, the baby will often smile back due to activation of mirror neurons (1).…”
mentioning
confidence: 99%